Keretapi Tanah Melayu (KTM) commuter : Railway transportation service satisfaction towards customers' loyalty / Amir Fikri Zawawi - Zawawi, Amir Fikri (Faculty of Business Management, 2017)
This research paper involves the investigation on customers' loyalty of Keretapi Tanah Melayu (KTM) commuter railway transportation service satisfaction. This research systematically analyzes some relevant literature regarding the underlying factors of service satisfaction on customers' loyalty with the service offered by KTM commuter in Malaysia. Several factors are identified that may give some impacts such as the costs or price offered, convenience, reliability of time, safety and station premises of KTM service. Railway transportation customers or passengers are more likely to be loyal as if the services provided are satisfying.